2014
DOI: 10.3109/02656736.2014.882021
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical trial of intravesical mitomycin-C and external deep pelvic hyperthermia for non-muscle-invasive bladder cancer

Abstract: Purpose This paper aims to evaluate the safety and heating efficiency of external deep pelvic hyperthermia combined with intravesical mitomycin C (MMC) as a novel therapy for non-muscle-invasive bladder cancer (NMIBC). Materials and methods We enrolled subjects with bacillus Calmette-Guérin (BCG) refractory NMIBC to an early phase clinical trial of external deep pelvic hyperthermia (using a BSD-2000 device) combined with MMC. Bladders were heated to 42 °C for 1 h during intravesical MMC treatment. Treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…Further, reoxygenation was associated with better clinical response in the locally advanced breast cancer study [32]. The prescribed temperature range for bladder heating is in the range of [42][43] C [33,34]. Thus it is unlikely that vascular damage to the tumour or normal tissue vasculature is a consequence.…”
Section: Increased Perfusion May Remove Drug From Target Volumementioning
confidence: 99%
“…Further, reoxygenation was associated with better clinical response in the locally advanced breast cancer study [32]. The prescribed temperature range for bladder heating is in the range of [42][43] C [33,34]. Thus it is unlikely that vascular damage to the tumour or normal tissue vasculature is a consequence.…”
Section: Increased Perfusion May Remove Drug From Target Volumementioning
confidence: 99%
“…Thermochemotherapy combining the direct antitumorigenic effect of local hyperthermia with a potentiated antitumorigenic cytostatic agent improves chemotherapy outcomes (19,30). However, conventional thermochemotherapy procedures do not allow precise and stable temperature control at the lesion sites, which hampers treatment efficacy (31)(32)(33)(34). We developed a 'BR-TRG-I type high-precision hyperthermic intraperitoneal perfusion treatment system', which allows precise automatic control of the temperature and perfusion rate of the drug solution.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot clinical trial using the BSD-2000 V R system, Inman et al reported outcomes of 15 patients with BCG refractory NMIBC, treated with external deep pelvic CHT [16]. All patients completed a 6-week induction course of BCG prior to their most recent recurrence, or were intolerant to BCG.…”
Section: Bsd-2000 Systemmentioning
confidence: 99%
“…The most common adverse events related to treatment with the BSD-2000 system were; urethral pain due to Foley catheter placement (40%), abdominal discomfort from the hyperthermia system (33%), irritative urinary symptoms from chemical cystitis (27%), and heat-induced induration or swelling of the abdominal skin (27%) [16].…”
Section: Bsd-2000mentioning
confidence: 99%
See 1 more Smart Citation